1994
DOI: 10.1111/j.1472-765x.1994.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus caprinus sp.nov., a tannin-resistant ruminal bacterium from feral goats

Abstract: An undescribed bacterium capable of clearing tannic acid‐protein complexes has been isolated from ruminal contents of feral goats browsing tannin‐rich Acacia species. The bacterium is a Gram‐positive facultative anaerobe, characterized as a Streptococcus, but DNA‐DNA hybridization and 16S rDNA sequencing show that it is distinct from the common ruminal species Strep. bovis. We propose the name Streptococcus caprinus for this species. The type strain is Strep. caprinus 2.3, Australian Collection of Microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 16 publications
5
75
1
2
Order By: Relevance
“…The stability of bands 1, 2, 6, and 9 with all legumes indicates presence of dominant and no sensible tannin-rich forages methanogens in the rumen liquor. Some cellulolytic bacteria (Brooker et al, 1994;Nelson et al, 1998), proteolytics (McSweeney et al, 1999, and fungi (Joblin et al, 2002) have already been identified as tannin tolerant.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of bands 1, 2, 6, and 9 with all legumes indicates presence of dominant and no sensible tannin-rich forages methanogens in the rumen liquor. Some cellulolytic bacteria (Brooker et al, 1994;Nelson et al, 1998), proteolytics (McSweeney et al, 1999, and fungi (Joblin et al, 2002) have already been identified as tannin tolerant.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous data have shown that bacteria can develop tolerance to tannins (5,36,37) and even degrade them (13). Likewise, previous research has shown that bacteria remain active even when the environmental temperature is sharply reduced (14,20), as would occur to fecal bacteria during excretion in a cold environment.…”
mentioning
confidence: 91%
“…some insects have thicker peritrophic membranes in the intestinal tract and mice, rats and deer show hypertrophy of the salivary gland, including secretion of tanninbinding proline-rich proteins (Makkar & Becker, 1998). In some feral ruminants, particularly goats and camels, tannin-resistant rumen microbial populations have been described (Brooker et al 1994), with the ability of feral goats and camels to digest tannin-containing forages being ascribed, at least in part, to the action of these microorganisms. Several tannin-tolerant or tannin-degrading bacterial species have now been isolated from a variety of sources worldwide (McSweeney et al 2001), and the existence of these micro-organisms appears to be a general phenomenon in animals adapted to a diet containing high levels of tannins.…”
Section: Tanninsmentioning
confidence: 99%